Relasi Islam dan Negara (Studi Politik Hukum di Indonesia) - Muhammad Chairul Huda (Yayasan Bina Darma, 2019)
This article describes about the relationship between Islam and the concept of state in the perspective of political law study in Indonesia. This is a philosophical juridical research by using qualitative methods. The data of this research are obtained from some literatures. The research findings show that there are three major thought about the relationship between Islam and state, namely; First, conservative thinking which places both religion and state (dien wa daulah). Second, secular thinking that separates both affairs namely state and religion. Third, moderate thinking which puts the Islamic values of universality into state system constitutionally and democratically. Law construction in Indonesia which is based on Pancasila is not contrary to Islamic law. The process of incorporating the values and spirit of Islamic law into the substance of law in Indonesia can be done through democratic political law in accordance with the constitution and legislation in Indonesia. The process that can be undertaken by Islamic law to put it into the substance of law in Indonesia is with prismatic law, an eclectic process, as well as through the national and regional legislation program.